Minimally invasive brow lifting techniques. Issue 5 (September 2017) - Broadbent, Talmage; Mohktarzadeh, Ali; Harrison, Andrew
Abstract : Purpose of review: Aesthetic concerns about upper eyelid and brow position are very common in ophthalmic practice. Management of brow descent and devolumization requires an approach customized to each patient taking into consideration preoperative examination and patient desires. This article will review several minimally invasive techniques that can be used to address the needs of patients with mild-to-moderate brow ptosis. Recent findings: Recent publications describe and analyse efficacy of several variations of browpexy techniques. Summary: Browpexy techniques provide a minimally invasive way to provide stabilization and modest elevation of the lateral brow. They can enhance outcomes of upper eyelid surgery in patients with both functional and cosmetic brow ptosis, who desire to avoid the cost and morbidity of more formal brow lifting techniques.